(Pro)renin Receptor Inhibition Reduces Plasma Cholesterol and Triglycerides but Does Not Attenuate Atherosclerosis in Atherosclerotic Mice - Ye, Dien; Yang, Xiaofei; Ren, Liwei; Lu, Hong S.; Sun, Yuan; Lin, Hui; Tan, Lunbo; Wang, Na; Nguyen, Genevieve; Bader, Michael; Mullick, Adam E.; Danser, A. H. Jan; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: Elevated plasma cholesterol concentrations contributes to ischemic CVD. Recently, we showed that inhibiting hepatic (P)RR attenuated diet-induced hypercholesterolemia and hypertriglyceridemia in LDLR deficient mice. The purpose of this study was to determine whether inhibiting hepatic (P)RR could attenuate atherosclerosis. Approach and Results: Eight weeks-old male LDLR-/- mice were injected with either saline or GalNAc-modified antisense oligos (G-ASOs) primarily targeting hepatic (P)RR and fed a western-type diet (WTD) for 16 weeks. (P)RR G-ASOs markedly reduced plasma cholesterol concentrations from 2211 ± 146 mg/dL to 1128 ± 121 mg/dL. FPLC analyses revealed that cholesterol in VLDL and IDL/LDL fraction were potently reduced by (P)RR ASOs. Moreover, (P)RR G-ASOs reduced plasma triglyceride concentrations by more than 80%. Strikingly, despite drastic reduction in plasma lipids, (P)RR G-ASOs did not attenuate atherosclerosis in these mice. Further testing in ApoE-/- mice confirmed that (P)RR G-ASOs reduced plasma lipid concentrations but not atherosclerosis. Transcriptomic analysis of the aortas revealed that (P)RR G-ASOs induced the expression of genes involved in immune response and inflammation. Further investigation revealed that (P)RR G-ASOs also inhibited (P)RR in macrophages and enhanced inflammatory response to exogenous stimuli. Moreover, deleting the (P)RR in macrophages accelerated atherosclerosis in WTD fed ApoE-/- mice. Conclusion: (P)RR G-ASOs reduced plasma lipids in atherosclerotic mice due to hepatic (P)RR deficiency. However, augmented pro-inflammatory responses in macrophages due to (P)RR downregulation counteracted the beneficial effects of lowered plasma lipids concentrations on atherosclerosis. Our study demonstrated that hepatic (P)RR and macrophage (P)RR play a counteracting role in atherosclerosis.